Challenges and Shortcomings of “Settlement Patterns Analysis” Studies in the Archaeology of Iran: A Critical Evaluation and Some Suggestions - Saeed Amirhajloo (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of the settlement pattern analysis in archaeology is to study the relationship between settlements and analyze the impact of environmental and cultural variables on the distribution, displacement, and evolution of the settlements and population changes over time. These studies have been developed by using combined and interdisciplinary methods. But there are some criticisms regarding the published research works on the mentioned subject in Iran, including inaccuracy of the field survey methods, focusing only on relative chronology, total ignoring of interdisciplinary sciences, satellite and aerial photos, remote sensing methods, the size of sites, taphonomic processes, statistical analysis methods, theories and methods of spatial analysis, and economic factors. Accordingly, it is suggested here that the data collection and analysis could be done by using the combined method that considers the following items: the study of historical texts, full coverage survey of the region, and attention to off-site archaeology especially in Neolithic studies, regarding absolute chronologies before going through the settlement pattern analysis, analysis of animal and plant remains, soil analysis and geophysical methods, statistical analysis, use of models and analysis of economic relations between settlements, and finally, the spatial analysis of settlements based on up-to-date theories and models.